STUDI TENTANG FUNGSI PENGAWASAN ATAS PENGUNGKAPAN CSR - Priscilla Ruth Putri; Hisar Pangaribuan (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to determine whether the supervisory function seen from the proportion of independent commissioners and independent audit committees has a significant influence on Corporate Social Responsibility (CSR). The samples used in this study were 53 samples of banks in Indonesia, Malaysia, and Singapore. The method used in this research is descriptive coefficient, coefficient of determination, correlation coefficient, and t test. The results of this study indicate that the independent board of commissioners has no effect on CSR disclosure with t count -0.038 < t table 1.65978 with is 0.05 or sig level. 0.704 is greater than 0.05 and the independent audit committee has no effect on CSR disclosure with t count 0.229 < t table 1.65978 with, 0.05 or sig level. 0.819 greater than 0.05